PEMBUATAN APOTIK HIDUP BERBASIS QR CODE UNTUK MENINGKATKAN LITERASI DIGITAL DAN PEMAHAMAN TANAMAN OBAT DI SMA NEGERI 2 MAKASSAR - Taiyeb, Mushawwir; Ayu, Resky; Hajar, Abdul; Fatmawati, Iin; Ma’ruf, Israeni Laila (Paramacitra Jurnal Pengabdian Masyarakat, 2025)
The QR Code-based Pharmacy Program at SMA Negeri 2 Makassar is a learning innovation that combines digital technology with the use of medicinal plants as contextual learning resources. This activity aims to improve students' digital literacy while deepening their understanding of medicinal plants through fast and interactive access to information using QR Codes. The program will be implemented from September 18 to November 26, 2025, involving students and teachers in medicinal plant planting activities and utilizing QR Codes to obtain digital information related to plants. The results of the implementation show various medicinal plants such as Ginger (Zingiber officinale), Galangal (Kaempferia galanga), Javanese ginger (Curcuma xanthorrhiza), White turmeric (Curcuma zedoaia), Chili (Capsicum sp.), Cayenne pepper (Capsicum frutscens), Coral cactus (Euphorbia lactea), Mother-in-law's tongue (Dracaena trifasciata), Aloe vera (Aloe vera), Variegated bone fracture (Euphorbia tirucali L.), Sambang colok (Ouret sanguinolenta), Malabar spinach (Basella alba), Aglonema lipstick (Aglaonema commutatum), Lemongrass (Cymbopogon citratus), Binahong (Anredera cordifolia), Kaffir lime (Citrus hystrix), Happy leaf (Dieffenbachia sp.), Ceriman (Monstera deliciosa), Blood leaf (Iresina herbstii), Chinese betel leaf (Paperomia pellucida). were successfully planted and given identity labels along with QR Codes containing scientific explanations. Students showed a positive response because QR Codes were considered easy, fast, and made learning more interesting. Thus, the QR Code-based Pharmacy program has proven effective in supporting contextual learning and improving digital literacy through direct learning experiences and interactive information access.